Tingkat Health Literacy Tentang Vaksinasi Covid-19 Mahasiswa Kesehatan Dan Non Kesehatan Di UIN Alauddin Makassar 2022 - Yustilawati, Eva; Gani, Nurul Fadhilah; Fitriani, Aidah; Hadrayani, Eka (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2023)
Background: Vaccination for Covid-19 is carried out to accelerate the handling of Covid-19. Individuals must have good health literacy in seeking information and making vaccination decisions, not only medical staff, but all people and students. Need to evaluate the level of understanding of health and non-health students related to health literacy. Methods: This research is a quantitative comparative study, cross sectional design. Participants totaled 500 students with details of 299 health students and 210 non-health students. Data was collected through a questionnaire using the HLQ (Health Literacy Questionnaire). Data were analyzed with the Kruskal Wallis test. Results: Based on statistical analysis, the health literacy level of UIN Alauddin Makassar students is in a good category with a mean mean value of 3-4. There is a difference in health literacy between health and non-health students (p-value 0.001). Domains that need to be improved in terms of finding the right health services and communication with health workers. Conclusion: there is a difference between health literacy between health and non-health students at UIN Alauddin Makassar and a strategy is needed to improve health literacy